If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4t=12+2t
We move all terms to the left:
4t-(12+2t)=0
We add all the numbers together, and all the variables
4t-(2t+12)=0
We get rid of parentheses
4t-2t-12=0
We add all the numbers together, and all the variables
2t-12=0
We move all terms containing t to the left, all other terms to the right
2t=12
t=12/2
t=6
| 28=7(11+u) | | 12y-(6y+8)=4y+2 | | 12y-(+8)=4y+2 | | 48+8x-2X=0 | | 3x+5x+1=0 | | 3=7m-8m | | 65(t/60)=60t+600/60 | | x/9=6/7 | | -2×-3=4x-5 | | 2.4z=1.2z-6.5=0.7 | | 14=p+3 | | (-2+5x)^2=9 | | -0.8k=-2 | | 10(1+10x)-10x=-10(11-8x) | | 31-8(y-5)=7 | | 3x-3=27-3x | | -6u/7=-24 | | 3v+5+2v=5 | | x+1,4x=24 | | 2.4x=0.3 | | 3x2+39+36=0 | | -6x=-64+3x | | 15=6x-5/2 | | 11-22x+8x+5=32 | | 250+25x=x+50 | | x-7=3x=16 | | 7x+5-3x=17 | | 3(2x+6)=8x+8-2x+10 | | y=-1/3+2 | | 3x2+33x+72=0 | | 5+3(3x-6)=6-5(2x+1) | | (G)X=-2x^2-5x-13 |